APPLICATION THE CONCEPT OF JUSTICE BASED ON AL-QUR'AN INTERPRETATION IN THE CONSTRUCTION OF INDONESIA'S LEGAL SYSTEM - Dewi Haryanti (International Journal of Law Reconstruction, 2020)
The purpose of this paper is to examine the application of the concept of justice based on the Qur'an’s interpretation in the construction of the Indonesian legal system. This research paradigm was the form of constructive design with analytical descriptive research specifications. Approach method used juridical empirical approach, it was used to view social symptoms related to the law and practice of legislation in Indonesia The focus of the problem in this paper was the different treatment between general inmates and corruption inmates in services and facilities in the prisons. Even in just one correctional institution, there are differences in room facilities between one another despite the fact that there are corrupt prisoners. It means that there is an injustice of the officials or authorities in giving the rights to prisoners. From the results of the research and discussion, it can be concluded that: 1) based on the Qur'an’s Interpretation, justice must be given to everyone without exception, including orders to be fair to the holders of power; 2) there are several components of the Indonesian legal system that still must be considered in the effort to uphold justice including the legal concept, the establishment of law, the form of law, and the application of the law. It is needed to revamp the intended system components, so that a system can run according to its purpose.